A fluorescent heteroditopic hemicryptophane cage for the selective recognition of choline phosphate1. Issue 13 (14th February 2015) - Zhang, Dawei; Gao, Guohua; Guy, Laure; Robert, Vincent; Dutasta, Jean-Pierre; Martinez, Alexandre
<x xml:space="preserve">Abstract</x> The first fluorescent hemicryptophane cage was synthesized and developed as an efficient and selective sensor for choline phosphate.